Blockchain for teens : with case studies and examples of Blockchain across various industries - Wu, Xun (Writer on Blockchain); Wu, Bridget (Apress L. P., 2023)
Similar to the Internet in the 1990s, Blockchain promises to revolutionize the world by reforming current business models. This book is a beginner-friendly guide for teens looking to build a basic foundation in Blockchain technologies. You'll start with an introduction to Blockchain, learn about the main features, and understand decentralization. Additionally, you'll get to know the current monetary system, major concepts in cryptography, and an overview of cryptocurrency. The book then explores various topics in Bitcoin, including its history, the consensus mechanism and the mining process. You'll also be introduced to non-fungible tokens (NFT)s, one of Blockchain's most well-known technologies, and delve into its different aspects, including the top NFT marketplaces. There is also a chapter about the Metaverse, another groundbreaking technology that will influence society throughout the next decade. You'll see how Crypto and NFTs enhance the Metaverse, and the relationship between Blockchain and the Metaverse. At the end of the book you'll review topics from previous chapters in a discussion on the future of Blockchain and conclude with an overview of real-life examples of Blockchain across various industries. What You'll Learn Examine the basics of Bitcoin and Ethereum Create your very own Bitcoin wallet Understand the concept of NFTs and build your first token Explore the Metaverse in Blockchain Envision the future of Blockchain This Book Is For Teens who are looking to build a basic understanding of Blockchain technologies.